Does Innovative Development Drive Green Economic Growth in Resource-Based Cities? Evidence From China - Zhang, Ming; Yan, Taihua; Ren, Qingzhong (Frontiers in Environmental Science, 2022)
With the increasingly urgent problems of ecological environmental governance and economic transformation, innovative development has become an inevitable choice for resource-based cities to realize green economic transformation. Based on the data of 108 resource-based cities in China from 2004 to 2018, this paper analyzes the effects of innovative development and resource endowment on green economic growth (GEG) by using a systematic GMM model. The findings are as follows: First, innovative development has a promoting effect on the green economic growth of resource-based cities, but its impact on different types of resource-based cities is heterogeneous. Innovative development has a promoting effect on the green economic growth of resource-based cities in the eastern region, comprehensive type, metal type, growth type, and regenerative type, and has an inhibiting effect on the green economic growth of resource-based cities in the northeast region, western region, oil and gas type, and non-metal type, but has no significant effect on the green economic growth of other resource-based cities. Second, the nonlinear effect of resource endowment on green economic growth of resource-based cities is not significant, but there is a "curse" effect of resource endowment on green economic growth. At the same time, the heterogeneity analysis shows that there are two kinds of "curse" and "blessing" effects of resource endowment on green economic growth in different types of resource-based cities. Third, the impact of innovative development on the green economic growth of resource-based cities is regulated by resource endowment. With the increase of resource endowment, the impact of innovative development on the green economic growth becomes less and less. Therefore, resource-based cities should continue to strengthen innovative development, optimize industrial policies, and promote coordinated regional development, so as to achieve sustainable development.